On the question of the formation of civic identity and ideology in a multiethnic region - D. Sh. Muftahutdinova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
The article discusses the formation of civic identity of Russia citizens. It shows on the basis of opinion polls a low degree of communication processes in the Volga Federal District and in the country as a whole. It shows on the basis of critical assessment of the common history book for secondary schools the need for education of respect to the historical heritage of the Russia citizens by means of history.